The VO2 slow component in swimming - Demarie, S.; Sardella, F.; Billat, V.; Magini, W.; Faina, M. (European Journal of Applied Physiology, 2001)
All studies on the oxygen uptake (V˙O2) slow component have been carried out for the sporting disciplines of cycling or running, but never for swimming. Considering that front crawl swimming is a sport discipline that is fundamentally different from both running and cycling, the aim of this study was to verify whether this slow component also appears in swimming. Six elite pentathletes were tested in a swimming flume while front crawl swimming to exhaustion. Swimming velocity for the slow component test was determined as v50<Delta>=CV+[(vV˙O2peak-CV)/2], where CV is the critical velocity and vV˙O2peak the lowest velocity at which peak V˙O2 occurred. To set the subject's CV, expressed as the slope of a straight line that describes the correlation between swimming distance and time, the record times over three swimming distances were recorded in a 50 m swimming pool. The vV˙O2peak was measured by means of an incremental test in the swimming flume. Gas exchange was measured by means of a telemetric metabolimeter (K4 RQ, Cosmed, Italy) that was connected to a snorkel. The slow component was found in all subjects, with a mean (SD) value of 239 (194) mlO2 · min-1. Therefore, although front crawl swimming is fundamentally different from both running and cycling, it appears that it also incurs a V˙O2 slow component. The origin of this phenomenon, however, is even more uncertain than for the other sport disciplines.